PEMAHAMAN DASAR AKUNTANSI BAGI SISWA-SISWI SMA KATOLIK SANTO KRITROFORUS 1 - JAKARTA - Hendro Lukman; Joan Yohanes; Phebe Callista (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Accounting science is a social science that is not fully related to social activities. Accounting is a social science that requires the math ability to study and understand it. The logic used in this science is similar to the exact sciences, because it requires a standard. Like other exact sciences, studying accounting requires routine, integrated exercises. Not all high schools can facilitate routine and integrated accounting practice activities. The same was experienced by Catholic High School St. Kristoforus 1 Jakarta. To improve the knowledge and skills of these high school students in the field of accounting, the